Uterine Cervical Cancer Prevention in Eritrea: Development and Results of a Pilot Project - Massimo Rugge; F.A.C.G; Michele Cosentino; Kebreab Mehari WG; Paola Bassan; Elisabetta Marcato; Zewdi Ghebremedhin Andemicael; Simon Gebrehiwet; Kibrom Hailu Ghebremicael; Tesfamariam Mehari Halki; Egle A Insacco; Gianlibero Onnis; et al. (Archives of Community Medicine and Public Health - Peertechz Publications, 2018)
Background: Uterine cervical cancer (UCC) is the fourth most common cancer worldwide; almost 85%-90% of UCCs, and UCC-related deaths occur in low-income countries. No UCC prevention programs are currently running in Eritrea. Aims: This manuscript describes a stepwise initiative aiming to establish an UCC prevention project in Eritrea, which combines Pap-smear and colposcopy. Methods: In 2013, an Italian multidisciplinary team submitted a project to the Eritrean Ministry of Health with a view to establishing an Eritrean-Italian UCC prevention task force. The project's starting point was an educational initiative to train local technicians on both Pap-smear assessments and colposcopy. Results: An intensive academic course organized by the University of Padova (Italy) under the patronage of the Eritrean Ministry of Health was successfully held in Asmara to train Eritrean technicians, nurses and midwifes to conduct Pap-smear assessments. Two subsequent pilot projects (2014-2016; 2016-2018) monitored the diagnostic competence of the Eritrean cyto-screeners. These pilot schemes resulted in an initial assessment of 2,014 Pap-smears, which provided information on the main operative issues involved in newly establishing a cancer prevention initiative in a sub-Saharan country. They also generated  preliminary data on the prevalence of cancer and precancerous cervical lesions. The second pilot study is additionally providing further insight on the problems faced in expanding the prevention project to the Asmara population as a whole. Conclusions: Anti-HPV vaccination, the most effi cient primary UCC prevention strategy, entails basic requirements that are not always available in low-income countries. In terms of secondary UCC  revention, this Eritrean experience suggests that the low cost of "Pap testing" and the availability of local human resources could lower the incidence of UCC and related deaths in Eritrea.